Cooperation in Preventing Crime at Sea of the Coast Police Forces of Vietnam and Southeast Asia Countries - A Case Study of the Crime of Pirate - Khanh, Nguyen Minh (Integrated Journal for Research in Arts and Humanities, 2024)
Maritime security is essential in protecting national territory and economic activities at sea. Southeast Asia is a vast sea with the busiest maritime route, making management and supervision difficult. According to the United Nations, Southeast Asian waters are the world's most dangerous territorial waters, accounting for 41% of piracy and armed attacks over the years, with losses of up to 8.4 billion a year. Based on different sources, the article presents the issue of cooperation between Southeast Asian countries in protecting the familiar sea. The study results show that countries that coordinate, share information, and cooperate will ensure good maritime security.